The effectiveness of dolomite and Ni-catalyst mixtures for pure H 2 production by methane steam reforming via CO 2 capture - Seitkaliyeva, Nurgul; Jand, Nader; Foscolo, Pier Ugo (Diffusion Fundamentals, 2007)
High hydrogen yields have been obtained continuously from steam reforming of methane coupled with simultaneous CO2 capture[1], at lower temperature (630oC) and pressure (1 atm) than those typical of traditional processes (800-900oC,15-30 atm), using calcined dolomite and a pulverized commercial Ni catalyst, in a single step. On the other hand, a pure CO2 stream is obtained by subsequent regeneration of the sorbent, which could be stored. A bubbling fluidized bed contained in a quartz vessel was operated batchwise. First, the durability of a dolomite in multi-cycle CO2 sorption/desorption runs has been investigated: a remarkable reduction of dolomite activity is observed after the first calcination, but substantially stable activity was conserved up to the fifth cycle. Then the performance of sorption enhanced catalytic steam reforming of methane to pure hydrogen has been evaluated. Two well distinct operation regimes have been found: before dolomite saturation, H2 concentration in the dry product gas remained stable at 94-96%, and CO2 was completely converted into calcium carbonate; after a short breakthrough period, concentration of H2 at the exit of the reactor reduced its value that became approximately equal to the equilibrium value expected for methane reforming and water gas shift reactions.